Effect of Phytase Supplementation on Growth Performance, Mineral Digestibility, and Tibia Calcium and Phosphorous in Broilers Fed Low Phosphorus Diets - W Iqbal; MA Yaseen; MA Rahman; SA Bhatti; MS Rahman; MU Yaqoob; F Ahmad; MU Zahid; M Shoaib (Brazilian Journal of Poultry Science, 2023)
ABSTRACT The aim of present study was to investigate the effect of phytase supplementation on growth performance, mineral digestibility, and tibia calcium and phosphorous in broilers fed low phosphorus diets. Three hundred broiler chicks were allotted to six different treatments with five replicates each (10 chicks/replicate). T1: Control, 0.5% available phosphorus (Av.P); T2: 0.35P, 0.35% Av.P; T3: 0.20P, 0.20% Av.P; T4: 0.35P-1Phy, diet 0.35P + 1000FTU/kg phytase; T5: 0.20P-2Phy, diet 0.20P + 2000 ftu/kg phytase; T6: 0.20P-3Phy, diet 0.20P + 3000 ftu/kg phytase. Feed intake and weight gain were higher (p=0.001) in broilers fed phytase supplemented diets. Feed conversion ratio was better (p<0.01) in the 0.35P-1Phy than in the others. Calcium and P digestibility was higher (p<0.05) in the 0.35P-1Phy than the 0.35P, 0.20P and 0.20P-2Phy, groups. The highest (p<0.05) tibia ash was observed in the 0.35P and 0.35P-1Phy groups rather than the 0.20P at 21st day, while at 33rd day it was higher (p<0.05) in the control than in 0.20P. At 21st day, tibia Ca content was higher (p<0.05) in the 0.35P-1Phy group as compared to 0.20P and 0.35P, while at 33rd day, tibia Ca content in the control and 0.20P-2Phy groups was higher (p<0.05) than that of 0.20P and 0.35P. Furthermore, tibia P content was higher (p<0.05) in all phytase supplemented groups. It could be concluded that dietary available phosphorus at 0.35% with phytase addition at 1000 FTU/kg reduces the cost per unit weight gain by 9.17%, with positive effects on growth performance.